Analyses of a datable solar eclipse record in Maya Classic period monumental inscriptions. (20th October 2021) - Hayakawa, Hisashi; Sôma, Misturu; Kinsman, J Hutch
ABSTRACT: Historical records of total solar eclipses provide vital information for computing the rotation of the Earth and understanding its long-term variations in the time before modern measurements. While eclipses recorded around Eurasia and North Africa for millennia have been subjected to consideration in this context, eclipse records in the American continents have received little attention. In this study, we analysed the solitary observational record for a solar eclipse conducted by the ancient Maya on 790 July 16 in the Julian calendar, recorded on the Stela 3 of Santa Elena Poco Uinic (N16°35′, W91°44′). This stela has an eclipse glyph and is associated with a total solar eclipse. Taking the up-to-date Earth rotation (Δ T ) rate into account, our calculations locate this site slightly out of the totality path. The visibility of the total solar eclipse from Santa Elena Poco Uinic would require Δ T to be 4074 s < Δ T < 4873 s. In comparison with the contemporary eclipse records, this yields a short-term increase in Δ T ≥ 800 s between 761 and 790 and a decrease in Δ T ≥ 580 s between 790 and 873. Therefore, the total solar eclipse on 790 July 16 cannot be expected to have been visible from Santa Elena Poco Uinic, unlike what has been previously considered. We conclude that this stela probably records a partial solar eclipse of great magnitude (≈0.946) visible under favourable meteorological conditions or is based on hearsay from the southern coastal area.